2018
DOI: 10.1093/bioinformatics/bty924
|View full text |Cite
|
Sign up to set email alerts
|

Improved inference of intermolecular contacts through protein–protein interaction prediction using coevolutionary analysis

Abstract: Motivation Predicting residue–residue contacts between interacting proteins is an important problem in bioinformatics. The growing wealth of sequence data can be used to infer these contacts through correlated mutation analysis on multiple sequence alignments of interacting homologs of the proteins of interest. This requires correct identification of pairs of interacting proteins for many species, in order to avoid introducing noise (i.e. non-interacting sequences) in the analysis that will d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…We first set out to automatically classify docking domains into classes, and to assess for which of these classes sufficient data is available to predict their protein-protein interactions (PPIs). The performance of coevolution-analysis-based PPI prediction depends highly on the alignment quality and shifts in interaction site can lead to mispredictions 26,43 . While a previous method 23 used joint alignment of the docking domains from all three compatibility classes 22 , new structural studies have shown that these docking domain classes have a markedly different tertiary structure and therefore should not be aligned 19,21,25 .…”
Section: A New Methods To Predict Pks Order In Assembly Linementioning
confidence: 99%
See 2 more Smart Citations
“…We first set out to automatically classify docking domains into classes, and to assess for which of these classes sufficient data is available to predict their protein-protein interactions (PPIs). The performance of coevolution-analysis-based PPI prediction depends highly on the alignment quality and shifts in interaction site can lead to mispredictions 26,43 . While a previous method 23 used joint alignment of the docking domains from all three compatibility classes 22 , new structural studies have shown that these docking domain classes have a markedly different tertiary structure and therefore should not be aligned 19,21,25 .…”
Section: A New Methods To Predict Pks Order In Assembly Linementioning
confidence: 99%
“…Second, considerable amounts of new data have been collected into standardized repositories 17 , making it possible to substantially expand the training sets. Third, we have recently developed a new computational method that reduces noise in coevolution-based intermolecular contact predictions 26 , leading to considerable improvements in distinguishing between protein-protein interactions and non-interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in PPI prediction (14)(15)(16)(17)(18) are highly welcome in the contexts of paralog matching, hostpathogen PPI network prediction and interacting protein families prediction. Recent studies suggest strategies like maximizing the interfamily coevolutionary signal (14), iterative paralog matching based on sequence "energies" (15) and expectation-maximization (18), which have been capable of accurately matching paralogs for some study cases. Despite these advances, the problem of PPI prediction remains unsolved for sequence ensembles in general, especially for proteins that coevolve in independent genomes though likely resulting from the same free-energy constraintsexamples are phage proteins and bacterial receptors, pathogen and host-cell proteins, neurotoxins and ion channels, to mention a few.…”
Section: Discussionmentioning
confidence: 99%
“…Second, considerable amounts of new data have been collected into standardized repositories 17 , making it possible to substantially expand the training sets. Third, we have recently developed a new computational method that reduces noise in coevolution-based intermolecular contact predictions 26 , leading to considerable improvements in distinguishing between protein-protein interactions and non-interactions. Here, we provide a new prediction pipeline, PKSpop, that exploits these new insights and developments, through automated recognition of docking domain classes, coevolutionary prediction of interaction probabilities between class I docking domains using expectationmaximization with the Ouroboros method 26 , and combining these results in a new algorithm that is usually able to predict a single most probable assembly line order.…”
Section: Introductionmentioning
confidence: 99%